The Induction of Resistance Against Verticillium Wilt of Olive by Previous Inoculation with a Low-Virulence Isolate of the Pathogen - Consuelo Martos-Moreno; Antonio Santos-Rufo; María del Carmen Raya-Ortega; Francisco Javier López-Escudero; Miguel Angel Blanco-López (Horticulturae)
Verticillium wilt of olive, caused by Verticillium dahliae Kleb., is a serious disease with no highly effective control methods currently available. Consequently, biological control strategies are being explored as viable and environmentally friendly alternatives. A natural recovery phenomenon has been observed in certain olive varieties following infection by low-virulence isolates of the pathogen, likely due to plant resistance mechanisms that may enhance defense against more virulent isolates. Based on these findings, a study was conducted to determine whether plants that had recovered from infection by a low-virulence isolate could exhibit increased resistance to highly virulent isolates. ‘Picual’ plants were first inoculated with a non-defoliating isolate, followed by inoculation with a defoliating isolate at different time intervals. The results demonstrate that prior infection with a non-defoliating isolate reduced disease severity caused by a defoliating isolate, particularly in susceptible cultivars like ‘Picual’. Treated plants exhibited slower disease progression and no mortality, whereas untreated plants developed severe symptoms and showed high mortality rates. A minimum interval of four months between inoculations with isolates of different virulence was crucial for achieving a significant reduction in disease severity. While this methodology has proven effective, further research is needed to elucidate the underlying mechanisms and identify additional biocontrol agents to enhance disease management strategies.